1997
DOI: 10.2527/1997.75123315x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of circulating peptides and assessment of peptide uptake across the gastrointestinal tract of sheep.

Abstract: Gastrointestinal absorption of peptides was examined in sheep fed a forage-based diet. Peptide concentrations were determined in arterial, portal, and mesenteric blood and plasma by quantification of amino acid concentrations before and after acid hydrolysis of samples that had been first deproteinized then subjected to Sephadex G-15 gel-filtration to remove residual protein. In contrast to other studies of ruminants, peptide concentrations for individual amino acids were lower than for the corresponding free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…In calves, for example, it has been shown that small peptides constituted 79% of total amino acid absorbed into portal vein in calves [9]. In sheep, however, no small peptide was found to be absorbed into portal vein [10]. Although differences in the results among these studies are attributable to species and diet, more important reason may be due to the inaccurate nature of the flux determination methods.…”
Section: Introductioncontrasting
confidence: 44%
“…In calves, for example, it has been shown that small peptides constituted 79% of total amino acid absorbed into portal vein in calves [9]. In sheep, however, no small peptide was found to be absorbed into portal vein [10]. Although differences in the results among these studies are attributable to species and diet, more important reason may be due to the inaccurate nature of the flux determination methods.…”
Section: Introductioncontrasting
confidence: 44%
“…In the present study with sheep fed fresh forage it accounted for 25 %. In sheep fed lucerne pellets (Backwell et al 1997;Bernard et al 2002) no significant flux of PAA across the PDV tissues could be detected. Combined, these data suggest that, in adult sheep, the significance of low-molecular-weight peptide net flux across the PDV is related to the nature of the diet.…”
Section: Daily Net Fluxesmentioning
confidence: 90%
“…Peptide absorption from the stomach was postulated to explain this phenomenon. However, in another study (Backwell et al 1997), no significant release of peptide amino acids was observed in the mesenteric vein or in the portal vein. Thwaites et al (1993) showed the presence of the proton-coupled peptide transporter in the epithelial tissues on both the apical and basolateral membranes in the gut.…”
Section: Discussionmentioning
confidence: 99%